PENDEKATAN HOLISTIK DALAM HAK ASUH ANAK PASCA PERCERAIAN: PERSPEKTIF MAQĀṢID SYARĪ’AH AL-TAHIR IBNU ASYUR - Fauzan, Ach.; Hamzah, Moh. (al-Rasῑkh: Jurnal Hukum Islam, 2024)
Divorce is a complex social phenomenon with significant impacts on various aspects of life, particularly concerning child custody issues. Given that child custody has long been a topic of special interest among Islamic scholars and intellectuals, this research aims to explore how a holistic approach to child custody after divorce can be formulated and implemented using Ibn Ashur's perspective of maqāṣid syarī’ah (objectives of Islamic law). This study is normative legal research utilizing a conceptual approach, with Miles and Huberman's analysis theory applied as the analytical technique. The findings of this study reveal that Ibn Ashur expanded the concept of maqāṣid syarī’ah by emphasizing the development and enhancement of human quality of life, beyond the traditional focus on mere protection. In the context of child custody after divorce, Islam emphasizes the child's well-being as the primary concern. The concept of hadhanah encompasses the fulfillment of the child's physical, emotional, and spiritual needs, with shared responsibility between both parents, even after divorce. The holistic approach to child custody inspired by Ibn Ashur's thought emphasizes the importance of considering the child's natural disposition (fitrah), flexibility in arrangements, maslahah (public interest) as the main principle, equality in parental roles, and respect for the child's freedom to express their opinions.